PENGARUH JENIS LEUKOSIT DAN JUMLAH TROMBOSIT DENGAN KEJADIAN TOKSOPLASMOSIS TERHADAP PEKERJA DI LINGKUNGAN HEWAN - Dinda Fadlliyah Dzikriana; Nur Kholifatul Hi’mah; Rahayu Anggraini (Universitas Nahdlatul Ulama Surabaya, 2020)
The incidence of toxoplasmosis is increasingly spread throughout the world include Indonesia. An estimated 15-85% of the world is infected with toxoplasmosis, a disease caused by Toxoplasma gondii and transmitted from animals to humans. Toxoplasmosis in immunocompetent people produces long-term immunity, whereas in immunocompromises cause pathological disorders to death. Immunocompetent cells consist of 5 types of leukocytes that are used as indicators of immune quality. Platelets also have a role as the immune system against pathogens and are toxic to T. gondii takizoit. This study was conducted with the aim to determine the effect of leukocytes and platelet count with the incidence of toxoplasmosis on workers in the animal environment with using 30 samples from workers at the Bratang Bird Market in Surabaya. Serological examination of Toxoplasma gondii IgG/IgM using the Rapid Immunochromatographic (ICT) test method, with the results of IgG(-)/IgM(-) as much as 13.3% and IgG(+)/IgM(-) as much as 86.7%. Whereas examination of leukocyte types and platelet count using Sysmex XP-300 type 3-part diff hematology analyzer with an average neutrophil value of 59% (normal), lymphocytes 31% (normal), and mixed (eosinophils, basophils, monocytes) 10% (increase). The results of the Spearman correlation test are that there is no influence between the type of leukocytes and the number of platelets with the incidence of toxoplasmosis on workers in the animal environment, because the p-value > 0.05 which not significant.